Effects Of Abbreviated Intensive Parent-Child Interaction Therapy On Noncompliance Behaviour Among Preschool Children With Attention And Deficit Hyperactivity Disorder - Noor Hassline Binti Mohamed
The aim of the study is to examine the effects of Abbreviated Intensive Parent-Child Interaction Therapy (PCIT) on noncompliance behaviour among preschool children who were diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). The sample for this study was six children who attended Special Education Integrated Programme under Ministry of Education Malaysia in Selangor and their parents. The Abbreviated Intensive PCIT is a brief and empirically-supported therapy for children with disruptive behaviour that places emphasis on improving the quality of parent child relationship and changing the ineffective way of parent-child interaction. Each parent was taught and coached in two types of parenting skills: Child Directed Interaction (CDI) and Parent Child Interaction (PDI). The A-B single-case experimental design was applied to test the effect of treatment throughout four different phases: Baseline (A,), Intensive Treatment (B-IT), Maintenance Treatment (B-MT) and Follow-up (FI). There were four research instruments: (i) Eyberg Child Behaviour Inventory (ECBI) used to measure the level of disruptive behaviour in children, (ii) Dyadic Parent-Child Interaction Coding System-111 (DPICS-111) used to measure parent's verbalisation and child compliance behaviour, (iii) Therapy Attitude Test (TAI) to measure parent's satisfaction towards the treatment, and (iv) open-ended question to explore parent's perception and experiences with the treatment. Parent's verbalisation and child compliance behaviours towards parental commands during these four phases were recorded and coded by the researcher and two trained assistants using DPICS-I11 coding instrument. Selecting the research sample was done using the purposive sampling which fulfilled the treatment inclusion and exclusion criteria for both parent and child. Based on the descriptive analyses, the findings of this study showed that Abbreviated Intensive PCIT was effective in reducing noncompliance behaviour among ADHD preschool children. These remained even after the follow-up test was conducted in which all dyads' scores for all instruments (ECBI and DPICS-111) during FI remained lower than their scores before treatment. The parent of Dyad 6 was achieved the mastery criteria for CDI and PDI skills. In addition, parents also reported high level of satisfaction toward the treatment. The findings suggested that, parenting module as one of the early intervention that based on the Abbreviated Intensive PCIT was effectively used to improve parent's positive parenting practices in reducing behavioural problems in the child. Main implications of the research findings involving cultural issues in the application of the treatment and several recommendations for future research were also discussed.